Agarose, Alginate and Chitosan Nanostructured Aerogels for Pharmaceutical Applications: A Short Review - Guastaferro, Mariangela; Reverchon, Ernesto; Baldino, Lucia (Frontiers in Bioengineering and Biotechnology, 2021)
In this short review, drug delivery systems, formed by polysaccharide-based (i.e., agarose, alginate and chitosan) aerogels, are analyzed. In particular, the main papers, published in the period 2011-2020 in this research field, have been investigated and critically discussed, in order to highlight strengths and weaknesses of the traditional production techniques (e.g., freeze-drying and air evaporation) of bio-aerogels with respect to supercritical CO2 assisted drying. Supercritical CO2 assisted drying demonstrated to be a promising technique to produce nanostructured bio-aerogels that maintain the starting gel volume and shape, when the solvent removal occurs at negligible surface tension. This characteristic, coupled with the possibility of removing also cross-linking agent residues from the aerogels, makes these advanced devices safe and suitable as carriers for controlled drug delivery applications.